ON TAX OBLIGATORY AND TAXPAYER AND ITS IMPLICATIONS - Leo B. Barus (Scientia Integritas Utama, 2022)
The scarcity of normative studies related to the terminology of taxpayers and taxpayers, many developed countries use the terminology of taxpayers, and the more substance taxpayers refer to in the decisions of the Constitutional Court, it is necessary to conduct a study of the terminology of taxpayers and taxpayers in order to produce legal concepts that are ideal. al to one of these terminologies. A ius constituen-dum is needed in forming a positive law that shows the formulation of a concept in a definitive, firm, and transparent manner so that it is sufficient to use normative legal methods. The terminology of the taxpayer has not met the requirements in the form of